Analisis Pengaruh Viral Marketing, Brand Image, dan Kualitas Produk Terhadap Purchase Intention : Studi pada Richeese Factory - Meylia Amanatul Rochma; Antok Supriyanto; Januar Wibowo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Richeese Factory is a company engaged in the Food and Beverage sector which has characteristics with spicy chicken and cheese sauce. This research aims to analyze the role of viral marketing, brand image and, product quality on purchase intention. This research is quantitative by distributing a questionnaire to more than 100 respondents who have bought Richeese Factory. Furthermore, the data is processed using the SPSS application. The results of this study show that brand image and product quality have a significant influence on purchase intention, while viral marketing does not have a significant influence on purchase intention. This study also shows that there are still other variables that can affect the purchase intention of Richeese Factory consumers besides viral marketing, brand image, and product quality.